The effect of information technology and service quality on customer loyalty of Bank Mandiri Jakarta Patra Jasa Branch - Faif Yusuf; Ahmad Taufik; Aris Hidayat (Privietlab, 2021)
The formulation of the problem in this study is whether there is a simultaneous influence of information technology and service quality on customer loyalty at Bank Mandiri's Jakarta Patra Jasa branch. The aim is to determine the effect of information technology and service quality simultaneously on customer loyalty at Bank Mandiri's Jakarta Patra Jasa branch. This research includes associative research which states the relationship between two or more variables. The sample taken in this study uses Simple Random Sampling with a total sample of 100 samples who are customers at PT Bank Mandiri (Persero), Tbk Patra Jasa Jakarta Branch. The data analysis method used was qualitative analysis, validity and reliability tests, multiple linear regression, f test (together test), and t test (partial test). The results of the study using multiple linear regression there is an influence between information technology and service quality simultaneously on customer loyalty . F test has an effect between information technology and service quality simultaneously on customer loyalty . The t test (partial test) has an influence between information technology on customer loyalty and there is an influence between customer satisfaction and customer loyalty.